QUARTZ C-AXES ORIENTATION DETERMINATION USING THE ROTATING POLARIZER MICROSCOPE - Fueten F.; Goodchild J.S. (My University, 2001)
A fast and accurate optical method to calculate quartz c-axis orientations using the rotating polarizer stage and standard thin sections is presented. c-Axis orientations are calculated for each pixel and Achsenverteilungsanalyse (AVA) can easily be constructed to study problems that would normally require a prohibitive amount of tedious work. The computer controlled rotating polarizer stage replaces the polarizer and analyzer of the standard petrographic microscope and allows a thin section to remain fixed while the polarizing filters are rotated by stepper motors. Data are collected by stepping the polarizers through a 180° rotation, capturing a frame at each step and extracting information on the intensity of the pixel and position of the polarizers. The position data are used to calculate the trend or trend+180° of the quartz c-axes, while a simple mathematical relationship between intensity and plunge is derived which allows the plunges of c-axes to be calculated.